KETIDAKADILAN GENDER DALAM KUMPULAN CERPEN BUKAN PERMAISURI KARYA NI KOMANG ARIANI SEBAGAI BAHAN AJAR SASTRA DI SMA - Sumarni Sumarni; Bayu Suta Wardianto; Heru Kurniawan (Bajang Institute, 2023)
This research aims to describe aspects of gender injustice in collection of short stories Bukan Permaisuri by Ni Komang Ariani and make them as additional literary teaching materials in high school. The research uses qualitative research methods. The data in the study was analyzed using content analysis techniques, data collection applying library techniques, simak techniques, as well as note-taking techniques. This study uses the validity of data involving related experts to make the research data more assured and objective. The findings of this study are four forms of gender inequality, including: (1) Subordination, (2) Stereotypes, (3) Violence, and (4) Double Workload. In addition, the collection of short stories used as analysis materials can be used as additional literary teaching materials in high school in accordance with the criteria for choosing teaching materials that have been set. Literary teaching materials from this collection of short stories are used in competency standards that are adapted to the indonesian language learning curriculum in high schools.